Count the ways: a novel (Harper Large Print, an imprint of HarperCollins Publishers, William Morrow, HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, 2021)
Eleanor and Cam meet at a crafts fair in Vermont in the early 1970s. She's an artist and writer, he makes wooden bowls. Within four years they are parents to three children, two daughters, and a red-headed son who fills his pockets with rocks, plays the violin, and talks to God. To Eleanor, their New Hampshire farm provides everything she always wanted: summer nights watching Cam's softball games, snow days by the fire and the annual tradition of making paper boats and cork people to launch in the brook every spring. If Eleanor and Cam don't make love as often as they used to, they have something that matters more. Their family. Then comes a terrible accident, caused by Cam's negligence. Unable to forgive him, Eleanor is consumed by bitterness, losing herself in her life as a mother, while Cam finds solace with a new young partner. Over the decades that follow, the five members of this fractured family make surprising discoveries and decisions that occasionally bring them together, and often tear them apart."